Characterization and functional analysis of prophenoloxidase system-associated genes from the black tiger shrimp penaeus monodon / Walaiporn Charoensapsri - Walaiporn Charoensapsri (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulaongkorn University, 2010